Preparedness for and perception of IFRS for SMEs: evidence from Turkey - Merve Kilic; Ali Uyar; Basak Ataman (Journal of Accounting and Management Information Systems (JAMIS), 2014)
The International Financial Reporting Standard for Small and Medium-sized Entities (IFRS for SMEs) is adopted by Turkey in November 2010. Turkey initially decided to apply IFRS for SMEs starting from 2013, but recently postponed application to 2014. This research has two primary purposes. The first is to analyse the awareness, information level, preparedness, and perception of the accounting professionals regarding IFRS for SMEs. The second is to examine the effect of several factors such as experience, education level, and preparedness of the accounting professionals on their perception of the IFRS for SMEs. For those purposes, a telephone questionnaire is administered to accounting professionals. The findings of the study show that most of the accounting professionals are aware of IFRS for SMEs adoption process; have a moderate information level of IFRS for SMEs; are optimistic regarding the adoption process; and attended trainings about IFRS for SMEs. Although the majority of the accounting professionals made some preparation for the IFRS for SMEs, there still is a considerable number of participants who did not. Respondents list as the advantages of IFRS for SMEs as comparability, reliability, transparency and understandability of financial statements and effective financial reporting. On the other hand, lack of training and costs are seen as the main obstacles to the IFRS for SMEs implementation. This study has some implications for several parties, including national and international standard authorities, regulatory bodies, managers, professionals, and academicians. National and international standard authorities should take into consideration the preparedness and perceptions of the parties while organizing the adoption process in their countries. Accounting professionals should make necessary preparations and inform their customers (entities) as early as possible for a successful adoption process. This research will make a significant contribution to the existing literature because the number of studies analysing the IFRS for SMEs adoption is small, especially in emerging countries.
Keywords: M41; M48; 650; IFRS for SMEs; preparedness; perception; accounting professionals; Turkey